2019
DOI: 10.3389/fped.2019.00255
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Tuberculosis in a Neonate: A Case Report and Literature Review

Abstract: Congenital tuberculosis (TB) is difficult to detect because the disease presents few or no symptoms in the fetus during pregnancy and nonspecific symptoms in neonates. We reviewed 20 cases of congenital TB reported between 2011 and 2017 and report a case of a mother and her 8 days old neonate with congenital TB. In these 21 cases (including our case), the most common clinical presentations were respiratory distress, fever, and hepatosplenomegaly. The most common chest imaging findings were pneumonia, multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
0
27
0
1
Order By: Relevance
“…Furthermore, 60%-70% of the mothers had no clinical manifestations of TB and were diagnosed after delivery [10]. Yeh et al reported a 2.2-fold increase in infant mortality in cases where the mothers had subclinical TB [11]. In the most recent analysis of 92 cases of congenital TB, the reported incidence of splenic TB at 12% and to our knowledge, there are only two cases on PubMed cases reports describing tuberculous peritonitis [10,[12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 60%-70% of the mothers had no clinical manifestations of TB and were diagnosed after delivery [10]. Yeh et al reported a 2.2-fold increase in infant mortality in cases where the mothers had subclinical TB [11]. In the most recent analysis of 92 cases of congenital TB, the reported incidence of splenic TB at 12% and to our knowledge, there are only two cases on PubMed cases reports describing tuberculous peritonitis [10,[12][13].…”
Section: Discussionmentioning
confidence: 99%
“…An animal with a chronic stage of the disease is known to be highly infectious and would likely serve as a good source of infection to a neonate by transmission in several possible ways. 17,18 Whether or not this was the case for the observed dam, it is still likely that her calf got infected in its first week of life, while suckling the colostrum and/or inhalating the aerosol produced by her. Attempt to generate strong evidence to establish transmission from the dam has not been successful due to failure to culture M bovis from the nasal swab sample; resampling of the dam was not possible as the animal was later culled without the knowledge of the authors.…”
Section: Discussionmentioning
confidence: 99%
“…An animal with a chronic stage of the disease is known to be highly infectious and would likely serve as a good source of infection to a neonate by transmission in several possible ways. 17,18 Therefore, it is highly likely that the calf in this observed case got infected in its first week of life, while suckling the colostrum by inhalation of aerosol primarily generated from its dam, although the possibility of transmission from other infected animals could not be ruled out as all reactors in this farm shared the same housing and husbandry system as the calf. In fact, the latter could explain why strains of the two spoligotype patterns were isolated from its lungs.…”
Section: Investigationmentioning
confidence: 94%